Complete genome sequence of Mycobacterium tuberculosis K from a Korean high school outbreak, belonging to the Beijing family. Issue 1 (December 2015) - Han, Seung; Song, Taeksun; Cho, Yong-Joon; Kim, Jong-Seok; Choi, Soo; Bang, Hye-Eun; Chun, Jongsik; Bai, Gill-Han; Cho, Sang-Nae; Shin, Sung
Abstract Mycobacterium tuberculosis K, a member of the Beijing family, was first identified in 1999 as the most prevalent genotype in South Korea among clinical isolates ofM. tuberculosis from high school outbreaks.M. tuberculosis K is an aerobic, non-motile, Gram-positive, and non-spore-forming rod-shaped bacillus. A transmission electron microscopy analysis displayed an abundance of lipid bodies in the cytosol. The genome of theM. tuberculosis K strain was sequenced using two independent sequencing methods (Sanger and Illumina). Here, we present the genomic features of the 4, 385, 518-bp-long complete genome sequence ofM. tuberculosis K (one chromosome, no plasmid, and 65.59 % G + C content) and its annotation, which consists of 4194 genes (3447 genes with predicted functions), 48 RNA genes (3 rRNA and 45 tRNA) and 261 genes with peptide signals.